2020
DOI: 10.1038/s41467-019-14256-1
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis reveals new evolutionary complexity in uveal melanoma

Abstract: Uveal melanoma (UM) is a highly metastatic cancer that, in contrast to cutaneous melanoma, is largely unresponsive to checkpoint immunotherapy. Here, we interrogate the tumor microenvironment at single-cell resolution using scRNA-seq of 59,915 tumor and nonneoplastic cells from 8 primary and 3 metastatic samples. Tumor cells reveal novel subclonal genomic complexity and transcriptional states. Tumor-infiltrating immune cells comprise a previously unrecognized diversity of cell types, including CD8 + T cells pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
368
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 341 publications
(390 citation statements)
references
References 39 publications
19
368
1
2
Order By: Relevance
“…Besides merely plotting a single list of genes, PieParty also allows for more complex visualizations. As an example, we used scRNA-seq data from uveal melanoma (UM) tumors to demonstrate a more complex application 4 . There are two main classes of UM tumors, class 1, which rarely metastasize, and class 2, which frequently metastasize and have a high mortality rate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides merely plotting a single list of genes, PieParty also allows for more complex visualizations. As an example, we used scRNA-seq data from uveal melanoma (UM) tumors to demonstrate a more complex application 4 . There are two main classes of UM tumors, class 1, which rarely metastasize, and class 2, which frequently metastasize and have a high mortality rate.…”
Section: Resultsmentioning
confidence: 99%
“…scRNA-seq data for testis and UM are publicly available 3,4 , and were downloaded, analyzed with Seurat (Version 3.2.2) as previously described 4 . The pure macrophage population was generated by extracting cells with CD68 expression > 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, it was exciting to observe benefits of our methods on both the scDNA-seq and the scRNA-seq data. Although RNA-derived copy number profiles may not be as accurate as those derived from DNAs, previous studies 54 suggested that they can reasonably distinguish tumor clones. Our study further revealed the value of scRNA-seq data in lineage tracing and supported the notion that genomic profiles, even approximations, are more accurate than transcriptomic profiles in determining biological timing of cells.…”
Section: Discussionmentioning
confidence: 97%
“…A similar phase I/II study on mRNA transfected autologous DCs in high-risk uveal melanoma patients has recently been closed due to slow accrual [ 105 ]. Immunotherapy with monoclonal antibodies, such as antiprogrammed cell death protein 1 (PD-1) nivolumab, anticytotoxic T-lymphocyte-associated Protein 4 (CTLA-4) ipilimumab, and anti lymphocyte activation gene 3 (LAG-3) relatlimab, modulated the immune responses in the tumor microenvironment and interfered with tumor growth and spread [ 106 , 107 ]. A small sample size phase I/II pilot trial of adjuvant ipilimumab in high-risk primary uveal melanoma demonstrated that 80% of patients were disease-free at 36 months [ 108 ].…”
Section: Adjuvant Therapies and Surveillance Of Ummentioning
confidence: 99%